Geometry of orientifold vacua and supersymmetry breaking - Thibaut Coudarchet; Emilian Dudas; Hervé Partouche (Journal of High Energy Physics, 2021)
Abstract Starting from a peculiar orientifold projection proposed long ago by Angelantonj and Cardella, we elaborate on a novel perturbative scenario that involves only D-branes, together with the two types of orientifold planes O ± and anti-orientifold planes O ¯ ± $$ {\overline{O}}_{± } $$ . We elucidate the microscopic ingredients of such models, connecting them to a novel realization of brane supersymmetry breaking. Depending on the position of the D-branes in the internal space, supersymmetry can be broken at the string scale on branes, or alternatively only at the massive level. The main novelty of this construction is that it features no NS-NS disk tadpoles, while avoiding open-string instabilities. The one-loop potential, which depends on the positions of the D-branes, is minimized for maximally broken, non-linearly realized supersymmetry. The orientifold projection and the effective field theory description reveal a soft breaking of supersymmetry in the closed-string sector. In such models it is possible to decouple the gravitino mass from the value of the scalar potential, while avoiding brane instabilities.